2021
DOI: 10.21608/ejhm.2021.200580
|View full text |Cite
|
Sign up to set email alerts
|

Post-Thoracotomy Pain: Review Article

Abstract: Background: Thoracotomy is a very painful surgical procedure that is used to get access into the pleural space, to the lungs, to the heart, to the esophagus or to get access to the thoracic aorta or anterior mediastinum. Objective: To study different modalities of treatment used for post thoracotomy pain control. Recent Findings: Inadequate post-thoracotomy analgesia enhances the postoperative stress response with deleterious effects on respiratory, cardiovascular, gastrointestinal, urinary, immune and coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The results of our study are in agreement with the results of the systematic review done by Badawy et al (16) who found that a multi-modal approach should be considered in the management of the post-thoracotomy pain starting even before the surgical trauma such as preemptive analgesia and the cognitive behavioral modalities.…”
Section: Resultssupporting
confidence: 92%
“…The results of our study are in agreement with the results of the systematic review done by Badawy et al (16) who found that a multi-modal approach should be considered in the management of the post-thoracotomy pain starting even before the surgical trauma such as preemptive analgesia and the cognitive behavioral modalities.…”
Section: Resultssupporting
confidence: 92%
“…Pain after thoracotomy is more severe and hemodynamic parameters are affected at a higher rate compared to other abdominal surgical interventions because of the extensive distribution of the intercostal nerves and incision of more muscle mass (Gad-Allah et al, 2021;Mesbah et al, 2016). Hypothermia, considered a frequent problem in the first postoperative hours, leads to feelings of cold, deterioration in thermal comfort, shivering, and pain (D. Kim, 2019;Riley & Andrzejowski, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thoracotomy is the first step in thoracic surgeries including pneumonectomy, lobectomy, lung segment resection, biopsies, and decortication or to get access for thoracic exploration in major trauma (Gad-Allah et al, 2021). Thoracotomy usually involves a skin incision in the fifth intercostal space, muscle dissection to variable degrees, and costal retraction (Kohli & Jain, 2020).…”
Section: Post-thoracotomy Painmentioning
confidence: 99%
“…Acute pain after thoracic surgery can caused by skin incisions, muscle splitting, intercostal nerve damage, pleural damage, chest drain insertion, retraction/resection/fracture of the ribs, or dislocation of the costovertebral joints [6]. Pediatric patients undergoing thoracic surgery show higher pain scores compared with those undergoing abdominal or extremity surgery [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients undergoing thoracic surgery show higher pain scores compared with those undergoing abdominal or extremity surgery [7]. Poorly treated pain in these patients can result, among other things, in atelectasis and pneumonia due to difficulty breathing deeply and coughing [6]. In addition, insufficient pain relief in the first 24 h after thoracic surgery is a risk factor for chronic pain [8].…”
Section: Introductionmentioning
confidence: 99%